2022
DOI: 10.1161/strokeaha.121.038403
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Joint Effects of Influenza-Like Illness and Vaccinations on Stroke in the Young: A Case-Control Study

Abstract: BACKGROUND: Influenza-like illness (ILI) is an acute trigger for stroke, although joint effects of vaccinations and ILI have not yet been explored. METHODS: Data for our case-control study was obtained from MarketScan Commercial Claims and Encounters between 2008 and 2014. Patients 18 to 65 years old who experienced a stroke were matched on age and admission date to a control, defined as patients with head trauma or ankle sprain at an inp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…14 An acute febrile illness was more common within 4 weeks among those who had a stroke (8.7%) than in controls (5.6%; aOR, 1.18 [95% CI, 1.01-1.39]). Consistent with the report by Vollmer et al, 12 influenza vaccination was associated with lower odds of all stroke (aOR, 0.53 [95% CI, 0.46-0.60]), ischemic stroke (aOR, 0.57 [95% CI, 0.50-0.67]), and hemorrhagic stroke (aOR, 0.34 [95% CI, 0.25-0.46]). Addressing the biological gradient Bradford Hill consideration, stroke risk was lower among those with 5 influenza vaccinations compared with those who had 1 to 4 vaccinations over the prior 5 years.…”
Section: See Related Article P 2585supporting
confidence: 90%
See 1 more Smart Citation
“…14 An acute febrile illness was more common within 4 weeks among those who had a stroke (8.7%) than in controls (5.6%; aOR, 1.18 [95% CI, 1.01-1.39]). Consistent with the report by Vollmer et al, 12 influenza vaccination was associated with lower odds of all stroke (aOR, 0.53 [95% CI, 0.46-0.60]), ischemic stroke (aOR, 0.57 [95% CI, 0.50-0.67]), and hemorrhagic stroke (aOR, 0.34 [95% CI, 0.25-0.46]). Addressing the biological gradient Bradford Hill consideration, stroke risk was lower among those with 5 influenza vaccinations compared with those who had 1 to 4 vaccinations over the prior 5 years.…”
Section: See Related Article P 2585supporting
confidence: 90%
“…The report by Vollmer et al 12 adds to this body of data. This case-control study using data from employee-sponsored insurance programs investigated the relationship between ILI, any type of vaccination, and the combined effects of ILI and vaccinations on stroke in young and middle-aged adults.…”
mentioning
confidence: 91%
“…Another case-control study found that having an influenza-like illness was not associated with stroke among those who received any vaccination (the majority likely for influenza; adjusted odds ratio, 1.07 [95% CI, 0.96–1.18]) but was associated with increased risk among the unvaccinated (adjusted odds ratio, 1.39 [95% CI, 1.32–1.47]; P for interaction <0.001). 10 Taken together, these and other studies suggest vaccination may be an effective strategy for reducing stroke risk.…”
mentioning
confidence: 75%
“…al reported higher stroke odds ratio following influenza infection compared to vaccination. 24 The clinical significance of the risk of stroke following vaccination must be carefully considered together with the significant benefits of receiving an influenza vaccination. Because the current framework of our SCCS study does not compare the vaccinated to the unvaccinated populations, it does not account for the reduced rate of severe influenza following vaccination.…”
Section: Discussionmentioning
confidence: 99%